Influence of Leadership and Motivation on the Work Performance of New Group Leaders at PT Pamapersada Nusantara Through Work Engagement - Ulin Nuha; Mufid Rosichin; Muhammad Indrik; Anita Maharani (The Islamic Education and Multiculturalism Foundation, 2023)
This research aims to determine the Influence of Leadership and Motivation on the Work Performance of New Group Leaders at PT Pamapersada Nusantara through Work Engagement. The sampling method used a probability sampling approach with a saturated sampling technique involving 220 respondents. Descriptive statistical methods were employed to analyze the data using the SmartPLS program. The results of this research indicate that: 1) Leadership has an impact on Work Performance. 2) Motivation does not affect Work Performance. 3) Leadership affects Work Engagement. 4) Motivation affects Work Engagement. 5) Work Engagement influences Work Performance. 6) Work Engagement mediates the relationship between Leadership and Work Performance. 7) Work Engagement mediates the impact of Motivation on the Work Performance of New Group Leaders at PAMA.